Adverse Effects of Monitoring: Evidence from a Field Experiment - Holger Herz; Christian Zihlmann (Center for Economic Studies and Ifo Institute (CESifo), 2021)
We conduct a field experiment with remote workers to assess potential adverse effects of monitoring. We find that monitoring reduces the average performance of workers, in particular among the intrinsically motivated workforce. Moreover, monitoring cultivates the average worker: There are fewer high performers and the variance in performance is significantly reduced. Importantly, we show that performance reductions primarily occur among challenging tasks. These performance reductions significantly increase unit costs in our setting. This effect is particularly severe when challenging tasks have high marginal value, as in high-performance work systems or when tasks are complementary inputs into the production function.
Keywords: C93; D21; J24; M50; 330; monitoring; hidden costs of control; remote work; field experiment